Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1016/j.mrfmmm.2011.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Epistasis analysis between homologous recombination genes in Saccharomyces cerevisiae identifies multiple repair pathways for Sgs1, Mus81-Mms4 and RNase H2

Abstract: The DNA repair genes SGS1 and MUS81 of Saccharomyces cerevisiae are thought to control alternative pathways for the repair of toxic recombination intermediates based on the fact that sgs1Δ mus81Δ synthetic lethality is suppressed in the absence of homologous recombination (HR). Although these genes appear to functionally overlap in yeast and other model systems, the specific pathways controlled by SGS1 and MUS81 are poorly defined. Epistasis analyses based on DNA damage sensitivity previously indicated that SG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 68 publications
4
17
0
Order By: Relevance
“…These genetic interactions, as well as the lack of genetic interactions between an rnh203⌬ mutation and mutations in other genes, were confirmed by measuring the doubling times of different double mutants and their respective single mutants (Fig. 2 With the exception of the 8 new genetic interactions identified here, our results agreed well with previously reported mutations that do or do not interact with deletions of genes encoding RNase H2 (44,61,(64)(65)(66)(67)(68)(69)(70)(71). In addition, other studies have indicated that strains lacking RNH203 require DEP1, DNA2, MMS4 (encodes a subunit of the Mus81-Mms4 complex), RMI1 (encodes a subunit of the Sgs1-Rmi1-Top3 complex), RNH1, and SMC6 for normal growth (20,41,44,58,72), although we did not investigate these interactions in the present study.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…These genetic interactions, as well as the lack of genetic interactions between an rnh203⌬ mutation and mutations in other genes, were confirmed by measuring the doubling times of different double mutants and their respective single mutants (Fig. 2 With the exception of the 8 new genetic interactions identified here, our results agreed well with previously reported mutations that do or do not interact with deletions of genes encoding RNase H2 (44,61,(64)(65)(66)(67)(68)(69)(70)(71). In addition, other studies have indicated that strains lacking RNH203 require DEP1, DNA2, MMS4 (encodes a subunit of the Mus81-Mms4 complex), RMI1 (encodes a subunit of the Sgs1-Rmi1-Top3 complex), RNH1, and SMC6 for normal growth (20,41,44,58,72), although we did not investigate these interactions in the present study.…”
Section: Resultssupporting
confidence: 91%
“…In aggregate, the results from our analysis suggest that RNase H2 defects cause an accumulation of mutagenic damage in DNA that is then repaired or compensated for by different DNA metabolism pathways. The rad51⌬-mediated suppression of the slow-growth phenotype of specific rnh203⌬ double mutants indicates that the loss of RNase H2 activity in these mutants causes increased DNA damage during DNA replication, leading to the formation of aberrant DNA structures (44,55,65,75). Defects in HR, sister chromatid HR and end resection (rad52⌬, mre11⌬, rad50⌬, xrs2⌬, esc2⌬, smc6, and potentially, esc4⌬/rtt107⌬ and ctf4⌬) (85)(86)(87)(88), and resolution of branched HR intermediates (mus81⌬, top3⌬, sgs1⌬, mms4⌬, and mph1⌬) (61,69) all caused slow-growth interactions with RNase H2 defects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNase H2-defective haploids, for example, have elevated gene conversion between closely linked repeats (Potenski et al 2014) and increased loss of markers flanked by direct repeats (Ii et al 2011). Although loss of either RNase H1 or RNase H2 promoted loss of an artificial chromosome, loss of both enzymes was required to elevate LOH on chromosome III in a diploid background (Wahba et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the specific case of recombination associated with highly elevated transcription, yeast strains with reduced RNase H activity generally exhibit elevated genomic instability. Haploid strains lacking RNase H2, for example, have increased recombination between direct repeats (Ii et al 2011;Potenski et al 2014). Top1 is required for this increase in recombination, suggesting that the initiating lesion is a Top1-mediated nick at an rNMP (Potenski et al 2014).…”
mentioning
confidence: 99%